The effects of protease supplementation on skeletal muscle function and DOMS following downhill running - Miller, P. C.; Bailey, S. P.; Barnes, M. E.; Derr, S. J.; Hall, E. E. (Journal of Sports Sciences, 2004)
Protease supplementation has been shown to attenuate soft tissue injury resulting from intense exercise. The aim of this study was to evaluate the effects of protease supplementation on muscle soreness and contractile performance after downhill running. Ten matched pairs of male participants ran at a -10% grade for 30 min at 80% of their predicted maximal heart rate. The participants consumed two protease tablets (325 mg pancreatic enzymes, 75 mg trypsin, 50 mg papain, 50 mg bromelain, 10 mg amylase, 10 mg lipase, 10 mg lysozyme, 2 mg chymotrypisn) or a placebo four times a day beginning 1 day before exercise and lasting a total of 4 days. The participants were evaluated for perceived muscle soreness of the front and back of the dominant leg, pressure pain threshold by dolorimetry of the anterior medial, anterior lateral, posterior medial and posterior lateral quadrants of the thigh, and knee extension/flexion torque and power. The experimental group demonstrated superior recovery of contractile function and diminished effects of delayed-onset muscle soreness after downhill running when compared with the placebo group. Our results indicate that protease supplementation may attenuate muscle soreness after downhill running. Protease supplementation may also facilitate muscle healing and allow for faster restoration of contractile function after intense exercise.